HUBUNGAN LAMA KERJA DENGAN KELUHAN GANGGUAN PERNAPASAN PADA PUMULUNG DI TPA SEI GILING KOTA TEBING TINGGI - Delita Br Panjaitan; Taufik Ashar; Nurmaini . (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2020)
Complaints of respiratory disorders are a sign of a disease that attacks the respiratory system that can occur for everyone. One of the factors that can affect someone experiencing complaints of respiratory distress is the length of time someone is exposed to a substance or objects in the work environment. Scavengers are one of the workers who are directly exposed to dangerous odors or gases that can cause complaints of respiratory problems. This study aims to determine the relationship of work duration with complaints of respiratory disorders in scavengers in Sei Giling Landfill in Tebing Tinggi City. This type of research is quantitative research with an analytic survey approach, using a cross sectional research design. This study uses a total sampling technique of 50 scavengers. Analysis of the data used is the Chi Square test. The results showed that there was a relationship between length of work (p value = 0.003) with complaints of respiratory disorders. Expected to scavengers to reduce exposure time at landfill and use personal protective equipment while in landfill.